2004
DOI: 10.1172/jci21851
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of tubuloglomerular feedback regulation of GFR in ecto-5′-nucleotidase/CD73–deficient mice

Abstract: Adenosine coordinates organ metabolism and blood supply, and it modulates immune responses. In the kidney it mediates the vascular response elicited by changes in NaCl concentration in the macula densa region of the nephron, thereby serving as an important regulator of GFR. To determine whether adenosine formation depends on extracellular nucleotide hydrolysis, we studied NaCl-dependent GFR regulation (tubuloglomerular feedback) in mice with targeted deletion of ecto-5′-nucleotidase/CD73 (e-5′NT/CD73), the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(98 citation statements)
references
References 38 publications
8
88
1
1
Order By: Relevance
“…eN has been deleted in at least three different laboratories. Knockout animals are healthy and display normal behavior [213][214][215]. In-depth experimental analyses of these animals underpinned the pathophysiological impact of eN and demonstrated that in the tissues investigated a significant amount of extracellular adenosine is derived from released nucleotide.…”
Section: Ecto-5′-nucleotidasementioning
confidence: 99%
“…eN has been deleted in at least three different laboratories. Knockout animals are healthy and display normal behavior [213][214][215]. In-depth experimental analyses of these animals underpinned the pathophysiological impact of eN and demonstrated that in the tissues investigated a significant amount of extracellular adenosine is derived from released nucleotide.…”
Section: Ecto-5′-nucleotidasementioning
confidence: 99%
“…The latter, being a suitable substrate for ecto-5′-nucleotidase, also expressed in the peritubular space, could then be converted to adenosine to cause or augment the vasoconstrictive response in TGF. Strong support for this scheme comes from the observation that ecto-5′-nucleotidase 'knockout' mice display a blunted TGF response [43,44]. Moreover, the response in wildtype mice is blocked by adenosine (A 1 ) receptor blockade [44].…”
Section: Ntpdase3mentioning
confidence: 99%
“…In the kidney, adenosine produced by epithelial cells of the macula densa, a group of modified epithelial cells in the distal convoluted tubule, in response to solute delivery is centrally involved in the regulation of glomerular filtration rate (GFR) (10,11). The net effect of adenosine in this process is to decrease GFR, primarily by stimulating vasoconstriction of afferent arterioles by activation of Adora1 on extraglomerular mesangial cells (10,11), but recent work also suggests a contribution to the decreased GFR of vasodilation produced by efferent arteriolar Adora2b (12).…”
Section: Generation Of Adenosine During Aki and Its Multiple Potentiamentioning
confidence: 99%